The Louisa Alcott Reader - Alcott, Louisa May (Saga Egmont, 2022)
"I'm so tired of Christmas I wish there never would be another one!"Nobody would be surprised if it were old Scrooge talking. But it's actually little Effie, a child with festive fatigue.Once you find out whether Effie dropped her impression of 'The Grinch', then you can go on a journey to 'Candy Country' or get to know 'Naughty Jocko' and find out more about 'The Piggy Girl'.A collection of 10 short children’s stories, brought to you by the iconic Louisa May Alcott. A winning compilation, perfect for youngsters from any generation.